EDUKASI MASYARAKAT AWAM PENGURUS GEREJA DALAM RANGKA MENINGKATKAN “STROKE AWARNESS” DI KOTA JAYAPURA - Bolly, Hendrikus Masang Ban; Sulelino, Renny; Sitanggang, Prysta Aderlia (Universitas Nusa Cendana, 2024)
A stroke is an acute attack due to blockage or rupture of blood vessels in the brain. Negligence and delay in fast and appropriate treatment will increase the death rate and permanent disability in patients with stroke. Education for promotive and preventive purposes related to stroke for church administrators is critical considering their roles and functions. This